Co-Creation of Public Service Innovation for Marginalized Groups in The Underdeveloped Regions - Nova Yulanda Putri Sipahutar; Metha Claudia Agatha Silitonga; Tyas Wahyu Fadhila; Rahayu Eka Putri; Yosefina Itu (Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Marginalized groups in underdeveloped regions still experience difficulties accessing public services. Co-creation of public service innovation is urgent to solve limited resources for providing public services to marginalized groups. This article aims to describe and analyze the type, influential actors, and influential factors of the co-creation of public service innovation for marginalized groups. This study applied a qualitative descriptive method with the research locus in the local governments of North Lombok Regency, Tojo Una-Una Regency, and Sorong Regency. Data were collected using in-depth interviews and FGD. North Lombok Regency was considered to have the most varied actors since they involved farmers group, trainers, non-governmental organizations, and the private sector to support the local government in co-initiating, co-designing, and co-implementing their innovations. Meanwhile, the Local Government of Tojo Una-Una Regency and Sorong Regency only involved the community in designing and implementing innovations. Further, the results of this study show that influential factors from several perspectives. From the government’s perspective, the local governments did not reflect the risk-averse but have shown an open attitude to co-creation. From the citizens’ perspective, concerns about the economic and health conditions of the marginalized people around them were their main motivation to participate in providing public services. Local governments should broaden the participation of actors to accelerate the target achievement.